2019
DOI: 10.1038/s41396-019-0449-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of virus-induced dissolved organic matter from picocyanobacteria: coupling of bacterial diversity and DOM chemodiversity

Abstract: Picocyanobacteria make up half of the ocean’s primary production, and they are subjected to frequent viral infection. Viral lysis of picocyanobacteria is a major driving force converting biologically fixed carbon into dissolved organic carbon (DOC). Viral-induced dissolved organic matter (vDOM) released from picocyanobacteria provides complex organic matter to bacterioplankton in the marine ecosystem. In order to understand how picocyanobacterial vDOM are transformed by bacteria and the impact of this process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 47 publications
8
98
0
Order By: Relevance
“…This is in accordance with other studies, showing that labile lysis products and virus particles were quickly metabolized, providing organic compounds and key elements to heterotrophic microorganisms [5,19,78]. In contrast to previous observations, N-containing compounds rather increased during the experiment [12]. The degradation of these molecules might have been masked by a constant input of amino acids and peptides due to leaching from the slurries.…”
Section: Viral Lysis and Subsequent Microbial Processes Were Imprintesupporting
confidence: 92%
See 2 more Smart Citations
“…This is in accordance with other studies, showing that labile lysis products and virus particles were quickly metabolized, providing organic compounds and key elements to heterotrophic microorganisms [5,19,78]. In contrast to previous observations, N-containing compounds rather increased during the experiment [12]. The degradation of these molecules might have been masked by a constant input of amino acids and peptides due to leaching from the slurries.…”
Section: Viral Lysis and Subsequent Microbial Processes Were Imprintesupporting
confidence: 92%
“…The decomposition of bulk organic compounds and molecules that were probably liberated by slurrying led to a gradual removal of bio-available components, accompanied by a relative accumulation of more refractory compounds [66,70]. Despite the clear alteration of the DOM composition by the slurry process, DOM analysis revealed that prophage induction had modified the chemical composition and character of the benthic DOM pool, which is in line with previous studies [12,20,71]. During virus-mediated cell lysis, the chemical complexity of DOM increased and resulted in the generation of compounds that were compositionally distinct from the bulk DOM.…”
Section: Viral Lysis and Subsequent Microbial Processes Were Imprintesupporting
confidence: 89%
See 1 more Smart Citation
“…Cyanobacteria possess both photosynthesis system I (PSI) and photosynthesis system II (PSII), and they usually perform oxygenic photosynthesis but can do anoxygenic photosynthesis (41,42). They are effective participants in marine carbon cycles (43). Cyanobacteria are found to inhabit multiple marine habitats, and Synechococcus spp.…”
mentioning
confidence: 99%
“…In addition to molecular approaches, some advanced chemical methods have been applied to virus-bacteria and virus-algae interactions in the marine environments. These include ultraviolet-visible absorbance, excitation emission matrix fluorescence, ultrahigh-resolution mass spectrometry and nuclear magnetic resonance spectroscopy (Zhao et al 2017(Zhao et al , 2019. The applications of these methods to photosynthetic biofilms will also significantly improve our understanding of the interactions between virus, bacteria and algae in the future.…”
Section: Methodological Considerationsmentioning
confidence: 99%